Reduced expression by SETBP1 haploinsufficiency causes developmental and expressive language delay indicating a phenotype distinct from Schinzel–Giedion syndrome. Issue 2 (30th October 2010) - Filges, Isabel; Shimojima, Keiko; Okamoto, Nobuhiko; Röthlisberger, Benno; Weber, Peter; Huber, Andreas R; Nishizawa, Tsutomu; Datta, Alexandre N; Miny, Peter; Yamamoto, Toshiyuki
Abstract : Background: Mutations of the SET binding protein 1 gene ( SETBP1 ) on 18q12.3 have recently been reported to cause Schinzel–Giedion syndrome (SGS). As rare 18q interstitial deletions affecting multiple genes including SETBP1 correlate with a milder phenotype, including minor physical anomalies and developmental and expressive speech delay, mutations in SETBP1 are thought to result in a gain-of-function or a dominant-negative effect. However, the consequence of the SETBP1 loss-of-function has not yet been well described. Methods: Microarray-based comparative genomic hybridisation (aCGH) analyses were performed to identify genetic causes for developmental and expressive speech delay in two patients. SETBP1 expression in fibroblasts obtained from one of the patients was analysed by real-time RT-PCR and western blotting. A cohort study to identify nucleotide changes in SETBP1 was performed in 142 Japanese patients with developmental delay. Results: aCGH analyses identified submicroscopic deletions of less than 1 Mb exclusively containing SETBP1 . Both patients show global developmental, expressive language delay and minor facial anomalies. Decreased expression of SETBP1 was identified in the patient's skin fibroblasts. No pathogenic mutation of SETBP1 was identified in the cohort study. Conclusion: SETBP1 expression was reduced in a patient with SETBP1 haploinsufficiency, indicating that the SETBP1 deletion phenotype is allele dose sensitive. In correlation with the exclusive deletion of SETBP1, this study delimits a milder phenotype distinct from SGS overlapping with the previously described phenotype of del(18)(q12.2q21.1) syndrome including global developmental, expressive language delay and distinctive facial features. These findings support the hypothesis that mutations in SETBP1 causing SGS may have a gain-of-function or a dominant-negative effect, whereas haploinsufficiency or loss-of-function mutations in SETBP1 cause a milder phenotype.